VD_FINDINFO HC / 2015 / 907 vom 20. Oktober 2015 - VD Tribunal cantonal (2015)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, ASSISTANCE JUDICIAIRE, DÉPENS, INDEMNITÉEN GÉNÉRAL | 105 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)